Notes on three braconid wasps (Hymenoptera: Braconidae, Doryctinae) parasitizing oak long-horned beetle, Massicus raddei (Coleoptera: Cerambycidae), a severe pest of Quercus spp. in China, together with the description of a new species - Cao, Liangming; Yang, Zhongqi; Tang, Yanlong; Wang, Xiaoyi (Zootaxa, 2015)
Three species of Doryctinae (Hymenoptera: Braconidae) parasitize larvae of oak longhorn beetle Massicus raddei Blessig (Coleoptera: Cerambycidae), a serious wood borer pest in North China. Rhoptrocentrus quercusi sp. nov., is described as a new species and Doryctes petiolatus Shestakov, as well as Zombrus bicolor (Enderlein). The three species are idiobiont ectoparasitoids, and may have potential for biological control of oak longhorn beetle.